An interaction controller formulation to systematically avoid force overshoots through impedance shaping method with compliant robot base. (November 2016) - Roveda, Loris; Pedrocchi, Nicola; Vicentini, Federico; Molinari Tosatti, Lorenzo
Abstract: Nowadays, light-weight manipulators are widely adopted in many applications requiring manipulation/interaction with compliant/fragile objects. Reduced inertia and controlled compliance, indeed, make such manipulators particularly attractive when compliant mountings (or mobile platforms) are adopted and contact force overshoot may compromise the application. The here presented work proposes the design of a force-tracking controller for interaction tasks allowing to systematically avoid any force overshoot for lightweight robots mounted on compliant bases. The developed algorithm allows to compensate for the compliant robot base dynamics that affects the interaction. The control gains are calculated to track a target force reference through the estimation of the robot base state and the interacting environment stiffness. Closed-loop stability and control gains calculation are described. The control law has been validated in a probing task involving a compliant robot base and a compliant environment to show the obtained performance.